Time‐varying volatility modelling of Baltic stock markets - Aktan, Bora; Korsakienė, Renata; Smaliukienė, Rasa (Journal of Business Economics and Management, 2010)
As time‐varying volatility has found applications in roughly all time series modelling in economics, it largely draws attention in the areas of financial markets. This study also examines the characteristics of conditional volatility in the Baltic Stock Markets (Estonia, Latvia and Lithuania) by using a broad range of GARCH volatility models. Correctly forecasting the volatility leads to better understanding and managing financial market risk. Daily returns from four Baltic stock indexes are used; Estonia (TALSE index), Latvia (RIGSE index), Lithuania (VILSE index) and synthetic BALTIC benchmark index. We test a large family of GARCH models, including; the basic GARCH model, GARCH‐in‐mean model, asymmetric exponential GARCH and GJR GARCH, power GARCH and component GARCH model. We find strong evidence that daily returns from Baltic Stock Markets can be successfully modelled by GARCH‐type models. For all Baltic markets, we conclude that increased risk will not necessarily lead to a rise in the returns. All of the analysed indexes exhibit complex time series characteristics involving asymmetry, long tails and complex autoregression in the returns. Results from this study are firmly recommended to financial officers and international investors. Baltijos vertybinių popierių rinkų nepastovumo modeliavimas Santrauka. Straipsnyje analizuojamas sąlyginis Baltijos vertybinių popierių rinkų (Estijos, Latvijos ir Lietuvos) nepastovumas, taikant eilę GARCH kintamumo modelių. Pažymėtina, kad tinkamai prognozuojant nepastovumą, galima geriau suvokti ir valdyti finansinių rinkų riziką. Straipsnyje remiamasi keturių Baltijos šalių kasdienėmis akcijų indeksų grąžomis; Estijos (TALSE indeksu), Latvijos (RIGSE indeksu), Lietuvos (VILSE indeksu) ir sintetiniu palyginamuoju BALTIC indeksu. Pritaikius eilę GARCH kintamumo modelių, galima teigti, kad didėjanti rizika Baltijos šalių rinkose nebūtinai įtakos vertybinių popierių grąžos augimą. Tyrimo metu gauti rezultatai rekomenduojami finansų specialistams ir investuotojams. Reikšminiai žodžiai: Baltijos vertybinių popierių rinkos, sąlyginis nepastovumas, GARCH modeliai, finansinė rizika, grąža. First Published Online: 10 Feb 2011